The Influence of Peer Relationships on Gadget Addiction at State Senior High School 5, Banda Aceh City - Panggabean , Dian Mahrani; Wardiati , Wahyu; Cibro , Elyza Ra'afianiama; Ulandari , Rahayu; Nelisma , Yuliana (Kamil : Journal of Education, 2025)
This study aims to analyze the relationship between peer relationships and gadget addiction among high school students at SMA Negeri 5 Banda Aceh. This study uses a quantitative method with descriptive observation and survey techniques. The results show that female students tend to have higher scores in terms of comfort in sharing problems and happiness with peers, while male students show lower scores in the positive influence of peers on their lives. Additionally, students who have positive social interactions with peers tend to have a lower likelihood of experiencing gadget addiction. Conversely, conflicts with peers can increase gadget use as an escape. This study also shows that the majority of students use gadgets for 8 hours or more per day and exhibit symptoms of gadget addiction such as FOMO (fear of missing out) and emotional dependence. The results of this study indicate that peer relationships play an important role in shaping students' social habits and gadget use. Therefore, it is essential for students to have healthy and balanced social relationships with peers to avoid the negative impacts of excessive gadget use